Central-Third Bone–Patellar Tendon–Bone Allografts Demonstrate Superior Biomechanical Failure Characteristics Compared With Hemi–Patellar Tendon Grafts. (November 2013) - Yanke, Adam B.; Bell, Rebecca; Lee, Andrew S.; Shewman, Elizabeth; Wang, Vincent M.; Bach, Bernard R.
Background: Reconstruction of the anterior cruciate ligament (ACL) is commonly performed with a bone–patellar tendon–bone (BTB) allograft. However, grafts may result from harvesting the central region of a whole graft (C-BTB), the medial 10 mm of a lateral hemi-BTB (L-BTB) graft, or the lateral 10 mm of a medial hemi-BTB (M-BTB) graft. Purpose: To quantify potential differences in graft biomechanical properties when comparing whole versus hemi-BTB grafts. Study Design: Controlled laboratory study. Methods: Ten pairs of human BTB allografts (irradiated with 1.0-1.2 Mrad) were randomized to preparation as whole grafts or hemigrafts. From these, 10-mm grafts were prepared from the center or the most central portion, respectively. After measurements of tendon thickness, width, and length, specimens underwent cyclic tensile testing, followed by load-to-failure analysis. Biomechanical outcomes included cyclic elongation and creep strain along with the following failure characteristics: maximum load, elongation at maximum load, maximum stress, strain at maximum stress, and linear stiffness. Results: Regionally, the mean thickness of the C-BTB (5.18 ± 0.75 mm), M-BTB (5.08 ± 0.56 mm), and L-BTB (5.32 ± 0.62 mm) grafts were comparable ( P > .72). Similarly, the mean length of the C-BTB (47.4 ± 6.73 mm), M-BTB (47.0 ± 5.45 mm), and L-BTB (50.7 ± 6.42 mm) grafts were alike ( P > .43). While differences in cyclic elongation and strain were not significant, the M-BTB graft tended to elongate more (0.204 ± 0.13 mm; P = .075) and experience greater strain (0.56% ± 0.32%; P = .054) compared with the C-BTB graft (0.09 ± 0.03 mm and 0.23% ± 0.07%, respectively). Load-to-failure testing demonstrated a higher maximum load (2293 ± 531 N) and stiffness (356 ± 46 N/mm) of the C-BTB graft as compared with the M-BTB graft (1575 ± 325 N [ P < .007] and 275 ± 37 N/mm [ P < .008], respectively) and L-BTB graft (1585 ± 452 N [ P < .008] and 277 ± 65 N/mm [ P < .009], respectively). No differences were noted with respect to elongation or stress at maximum load among the grafts. Maximum stress in the C-BTB graft (45.4 ± 11.5 MPa) was greater than in the L-BTB graft (29.7 ± 10.6 MPa) ( P < .03) and tended to be greater than the M-BTB graft (34.1 ± 6.27 MPa) ( P = .087). Conclusion: Biomechanical failure properties (maximum load, stress, and stiffness) of the central portion of a whole BTB graft are superior to those of the medial portion of a lateral hemi-BTB graft and the lateral portion of a medial hemi-BTB graft. However, cyclic loading characteristics did not differ between grafts. Clinical Relevance: Although the true central-third BTB graft is biomechanically superior to hemi-BTB grafts, future studies are necessary to determine if the use of hemigrafts leads to an increased incidence of clinical failure.